Sustainable Curbing Of Youth Restiveness In IMO State: The Strategic Role Of Entrepreneurship Development - A., Emerole Gideon; Chikwe, Goddey C.; Augustus-Daddie, Joel (Archives of Business Research, 2018)
this study examined Curbing Youth Restiveness in Imo State: The Strategic Role of Entrepreneurship Development. The descriptive survey research method was adopted and the study covered a population of 1396 people randomly selected from 20 autonomous communities from the two oil bearing Local Government Areas in Imo state, representatives of community based Non-governmental organizations that are involved in youth capacity development, security experts and scholars of sociology and rural development. Data was generated through a five point likert scale questionnaire from a sample of 311 respondents chosen using the Taro Yamene method. The hypotheses were tested with kruskawalis test (H) with the aid of the 23.0 version of statistical package for social sciences (SPSS) based on the 279 questionnaires validly filled and returned. The study concluded that the fight against youth restiveness and indeed all social vices in Imo state in particular and Nigeria at large must be reorganized to adopt proactive and preventive measures through the expansion of the nation’s economic space for youth’s inclusiveness, especially youths in rural areas whose access to functional and quality education is very limited. This can only be achieved if entrepreneurial development is giving active attention and not mere lip service. Furthermore, a comparative look at the results obtained (i.e EKCD 0.001 and AF 0.002) shows that sharing money to youths without giving them functional entrepreneurial skills does not create the needed sustainable route to curbing restiveness. It was recommended that to curb restiveness, youths empowerment should focus more on entrepreneurial knowledge creation and sharing than sharing of funds without tagging them to productive economic projects, school curriculum should be revised to embrace entrepreneurship development and that attention should be giving to vocational education through the establishment and adequate funding of vocational institutions that equips the youths with contemporary marketable entrepreneurial skills